LANDSLIDE HAZARD LEVEL IN PASURUAN REGENCY - Turningtyas Ayu Rachmawati; Adi Susilo; Dwi Rahmawati; Yunita Ratih Wijayanti (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Pasuruan Regency is an area with potential for landslides, particularly along the Arjuno-Welirang Slope and the Bromo Tengger Semeru National Park (TNBTS). Geographical conditions, high slopes, and andosols and litosols that are easily eroded, further exacerbated by human activities such as land-use changes, lead to increasingly high landslide potentials. The TNBTS Area and Arjuna-Welirang Mountains are priority destinations for national tourism. Therefore, efforts for disaster risk reduction are imperative. Assessment of landslide hazard levels is necessary as a basis for landslide mitigation. The analysis used to assess landslide susceptibility was the overlay of two maps: a map of landslide-potential zones and a map of potential runout zones produced from the model by Horton et al. (2008) employing the flow direction algorithm. Analysis results indicate that landslide hazards in Pasuruan Regency mostly comprise the low hazard (29,924.73 hectares), followed by high landslide hazard (17,421.39 hectares), and moderate landslide hazard (2,161.8 hectares). The high hazard level is found in Tosari District due to being located close to Mount Bromo, whereas low hazard levels are mostly seen in lowland areas.